Evaluate the integrative effects of irrigation water level, furrow irrigation methods, and nitrogen fertilizer rate on tomato yield in semi-arid southern Ethiopia - Edmealem Temesgen Ebstu; Mekuanent Muluneh (Heliyon)
This study investigates the integrative effects of irrigation water management allowable depletion (MAD), furrow irrigation methods (FIM), and nitrogen fertilizer application rate (NFAR) on tomato yield components. These yield components include marketable, unmarketable, and total yield. Additionally, the study examines crop agronomy components such as plant height, number of branches, and root depth in semi-arid Southern Ethiopia. The research employs a factorial and split-plot design. Three types of FIM are assigned as the main plot, while three levels of irrigation water (50 %, 75 %, and 100 % MAD) and four levels of NFAR (0 %, 50 %, 100 %, and 150 % NFAR) serve as the subplots, with three replications. The study results reveal significant impacts of these factors. All p-values for tomato yield and agronomy-measured components are less than 0.05. FIM, irrigation water level, and NFAR interaction affect marketable, unmarketable, and total tomato yield. The results ranged from 2.3 tons ha⁻1–43.9 tons ha⁻1 for marketable yield, 0.8 tons ha⁻1–8 tons ha⁻1 for unmarketable yield, and 6.3 tons ha⁻1–45.2 tons ha⁻1 for total yield. The integration of 75 % MAD with 100 % NFAR under conventional furrow irrigation, and 100 % MAD with 100 % NFAR under alternative furrow irrigation, was most preferable. This approach resulted in no loss of nitrogen fertilizer and saved 25 % of irrigation water without reducing tomato yield. However, the interaction of deficit nitrogen fertilizer rate application, with or without full application of MAD and conventional or other furrow irrigation methods, caused the total yield to decrease. CFIM and AFIM with 100 % MAD and 100NFAR treatments yielded the highest profits, while the FFIM approach under 50%MAD and 0%NFAR conditions negatively impacted profitability. Therefore, by adopting the preferable practices, farmers can achieve higher productivity and sustainability in tomato cultivation. This approach addresses the challenges posed by water scarcity and nutrient limitations.